An Inexpensive, Lightweight Percussion Core Sampling System - Reasoner, Mel (Géographie physique et Quaternaire, 1986)
ABSTRACTThe assembly and operation of lightweight, percussion coring equipment designed for the recovery of lacustrine sediments are described. Two ropes are employed in the operation of the system which is conducted from the surface of the ice pack. The main line is used to raise and lower the core barrel assembly and a secondary line operates the driver. The driver is guided to the core barrel assembly by the main line. The mechanical advantage required for core removal is obtained from a simple pulley system anchored to the surface of the ice pack. The equipment can be transported and operated by one person in the field and is theoretically unrestricted by water depth. The equipment was successfully tested under winter conditions and recovered 7.6 cm diameter core samples up to 257 cm in length.